A new metal–organic open framework enabling facile synthesis of carbon encapsulated transition metal phosphide/sulfide nanoparticle electrocatalysts. Issue 12 (8th March 2019) - Weng, Baicheng; Wang, Xiaoming; Grice, Corey R.; Xu, Fenghua; Yan, Yanfa
Abstract : A new metal–organic framework enables a facile and scalable synthesis of transition metal phosphide and sulfide nanoparticle encapsulated by heteroatom-doped carbon as bifunctional electrocatalysts for water splitting. Abstract : Engineering 3d to 5d nonprecious transition metal electrocatalysts to demonstrate both high activity and superior durability for both the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), which would be ideal for enabling low-cost hydrogen production from water splitting, remains a serious challenge. Herein, we report the rational design and experimental realization of a new metal–organic open framework (MOF) to enable a facile and scalable synthesis of transition metal phosphide (TMP) and sulfide (TMS) composite nanoparticle electrocatalysts encapsulated by heteroatom-doped carbon (TMP/C and TMS/C) as bifunctional electrocatalysts for water splitting. Using this new MOF, we synthesized NiP/NiFeP/C and MoWS/MoP/C composite nanoparticle electrocatalysts that exhibited outstanding electrocatalytic activities and durability that are among the higher values reported in the literature for HER and OER electrocatalysts. A two-electrode water-splitting device using our bifunctional NiP/NiFeP/C catalyst reached 10 mA cm −2 at a cell voltage of 1.53 V and 100 mA cm −2 at 1.68 V in 1.0 M KOH. The device showed excellent stability for overall water splitting with almost 98% retention of its initial current of 100 mA cm −2 for over 20 h. Our results demonstrate the versatility of the new MOF to synthesize highly active and stable TM-based electrocatalysts for water splitting.